Exploring the angiographic-biologic phenotype in the IMAGINE study: quantitative UWFA and cytokine expression. Issue 10 (7th June 2021) - Abraham, Joseph R; Wykoff, Charles C; Arepalli, Sruthi; Lunasco, Leina; Yu, Hannah J; Martin, Alison; Mugnaini, Christopher; Hu, Ming; Reese, Jamie; Srivastava, Sunil K; Brown, David M; Ehlers, Justis P
Abstract : Background: This study investigates the association of intraocular cytokine expression and ultrawide-field fluorescein angiography (UWFA) quantitative imaging biomarkers and their association with angiographical feature response after antivascular endothelial growth factor (VEGF) therapy in diabetic macular oedema (DME). Methods: The IMAGINE DME study is a post hoc imaging biomarker and intraocular cytokine assessment from the DAVE study, a prospective DME clinical trial that included aqueous humour sampling and UWFA imaging. Fifty-four cytokines associated with inflammation and angiogenesis were evaluated through multiplex arrays. UWFA parameters were assessed using an automated feature analysis platform to determine ischaemic and leakage indices and microaneurysm (MA) count. Eyes were classified into UWFA responder or non-responder groups based on longitudinal quantitative UWFA parameter improvement. Cytokine expression was correlated with UWFA metrics and evaluated in the context of therapeutic response. Results: Twenty-one eyes were included with a mean age of 55±10 years. Increased panretinal leakage index correlated with VEGF (r=0.70, p=0.0005), angiopoietin-like 4 (r=0.77, p=4.6E-5) and interleukin (IL)-6 (r=0.64, p=0.002). Panretinal ischaemic index was associated with tissue inhibitor of metalloproteinases 1 (TIMP-1, r=0.49, p=0.03) and peripheral ischaemia correlated with VEGF (r=0.45, p=0.05). MA count correlated with increased monocyte chemotactic protein-4 (MCP-4, r=0.60, p=0.004) and platelet and endothelial cell adhesion molecule 1 (PECAM-1, r=0.58, p=0.005). Longitudinal MA reduction was associated with decreased baseline VEGF and urokinase receptor (uPAR) (p<0.05). High baseline VEGF and IL-6 were associated with dramatic reduction in macular leakage (p<0.05). Conclusions: Baseline and longitudinal quantitative UWFA imaging parameters correlated with multiple aqueous humour cytokine concentrations, including VEGF and IL-6. Further research is needed to assess the possible implications of using these findings for evaluating treatment response.